Measuring users' satisfaction towards student-based information systems in a selected institute of higher learning/ Sarina Ahmat, Saidatul Akmar Ismail and Nur Adlina Zulkifli - Ahmat, Sarina; Ismail, Saidatul Akmar; Zulkifli, Nur Adlina (Faculty of Information Management, 2021)
Information Systems become one of the most vital applications to reduce human-errors in any organization. The usage of information system sped up as human knowledge expanded. Thus, the management of human knowledge is much easier now through the systems application. Various applications of invention help employees and network users to work effectively and save cost and time efficiently. This study was an attempt to determine users' satisfaction towards student-based information system. The positivism method and deductive approach were chosen for as the research paradigm. Data gathered from the selected respondents through the survey using the questionnaire as a research instrument. The study took place at the Grand Premier Institute of Higher Learning among the undergraduate students and administrative staff at faculties. In this research, the sample size was 262 out of 8300 population size, using simple random sampling as a sampling technique. Finally, an analysis of data conducted using the Statistical Package for the Social Science (SPSS) function of descriptive statistics, reliability analysis, and parametric test as the data analysis approach.